Cognitive Impairment and Tramadol Dependence. Issue 1 (February 2017) - Bassiony, Medhat M.; Youssef, Usama M.; Hassan, Mervat S.; Salah El-Deen, Ghada M.; El-gohari, Hayam; Abdelghani, Mohamed; Abdalla, Ahmed; Ibrahim, Dalia H.
Abstract: Background and Objective: Cognitive impairment is one of the consequences of substance abuse. Tramadol abuse is a public health problem in Egypt. The objective of this study was to estimate the prevalence and correlates of cognitive impairment among tramadol-abuse patients and control subjects. Methods: This study included 100 patients with tramadol abuse and 100 control subjects (matched for age, sex, and education) who were recruited from Zagazig University Hospital, Egypt. Patients were divided into 2 groups: patients who used tramadol only (tramadol-alone group) and patients who used tramadol and other substances (polysubstance group). The participants were interviewed using Montreal Cognitive Assessment test and had urine screening for drugs. Results: Twenty-four percent of the cases used tramadol alone, whereas the remaining used tramadol and other substances, mainly cannabis (66%) and benzodiazepines (27%). Tramadol-abuse patients were about 3 times more likely to have cognitive impairment than control subjects (81% vs 28%). Tramadol-alone patients were more than 2 times more likely to have cognitive impairment than control subjects (67% vs 28%). Cognitive impairment was significantly associated with polysubstance abuse. There was no association between cognitive impairment and sociodemographic or clinical factors. Conclusions: Cognitive impairment occurs commonly among tramadol-abuse patients. Memory impairment is the most common cognitive domain to be affected. There is a significant association between cognitive impairment and polysubstance abuse.